Open innovation and the effects of Crowdsourcing in a pharma ecosystem - Irene Christensen; Christer Karlsson (Journal of Innovation & Knowledge (JIK), 2019)
This study examines the emerging organizational concept of Crowdsourcing where new idea submissions from outside the firm's boundaries are obtained, selected, evaluated, coded, and integrated into the organization. This research is developed through a case study of a large European pharmaceutical company 'PharmaFX', we investigate the process of the interactions between the host company and its collaborators. The Crowdsourcing activities conducted in 2014 and 2015 are presented and acquired benefits are reported on from the perspective of transaction cost. One of our central findings provide newly discovered evidence that the process of "scientific Ideation Challenge" as seen planned and implemented in PharmaFX in collaboration with InnoCentive - a reputable Crowdsourcing platform intermediary - have unique process characteristics, became less economically viable for PharmaFX than anticipated, this was partly due to the broadness of the scope of the Crowdsourcing initiatives. These findings could have a significant impact on future open innovation strategies and their economic viability in drug development.
Keywords: O32; 650; Crowdsourcing; Drug discovery; Pharmaceutical industry; Transaction cost theory